PERANCANGAN SISTEM INFORMASI PENGGAJIAN BERBASIS WEBSITE PADA PT BPR NUSANTARA BONA PASOGIT 12 - Pras Parman Wau; Kecitaan Harefa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The payroll system is a system that can help companies manage matters relating to employee salaries, as well as to record and store employee salary payment data within an organization or company. A payroll system is needed in a company to manage the salaries or wages of employees in that company. The system currently in use at PT. Nusantara Bona Pasogit 12 still uses conventional systems or Microsoft Excel so that payroll data is not archived optimally. To handle this, a special application is made that is used to manage and record various employee payroll transactions that will be paid. Payroll information system application that can generate or manage employee salary data, employee absences and overtime. This application was created using the waterfall method. The results of this payroll system application design indicate that the role of computer applications in information systems is very important as a support in improving the quality of data processing activities, collecting employee salaries in a company. To increase work effectiveness and provide information quickly and accurately, this application was built with the PHP programming language and MySql as a database, using the Unified Modeling Language (UML) tools.